Factors Associated with Reproductive Age Couples’ Selection of Sterilization in the Era of the National Health Insurance Program - Nugroho, Achmadi S; Azhari, Azhari; Nurtjahyo, Awan; Theodorus, Theodorus (Indonesian Socety of Obstetrics and Gynecology, 2019)
Objective:To assess factors associated withselection of contraceptive sterilization in reproductive age couples in Dr. Mohammad Hoesin Palembang hospital in the era of BPJS. Methods: This cross sectional study was conducted between January - December 2017. Study sample was reproductive age couples (RAC) who were married and came to P2 UGD, maternity room and midwifery ward of Dr. Mohammad Hoesin Palembang hospital and metour inclusion criteria. All study participants were given a questionnaire to assess factors that influence selection of contraceptive methods in women. Data were analyzed using SPSS software version 17. Results: We found a significant relationship between number of children (PR = 3,988; p = 0.016), knowledge level (PR = 3,893; p = 0,024) and husband support (PR = 5,233; p = 0.009) with sterilization contraceptive selection. In addition, there were no significant correlation between age (PR = 2,311, p = 0,210), education level (PR = 1,893, p = 0,331), woman attitude (PR = 1,567, p = 0,758), availability of contraception ( (PR = 1,969, p = 0,342), officer attitude (PR = 1,088, p = 0,000) and information given by officer (PR = 1,378; p = 0,719) 1,310; p = 0.802) with selection of sterilization. With logistic regression test, we found that husband support was the most important factor to selection of sterilization contraception (PR = 4,266, p = 0,040) followed by knowledge (PR = 3,620, p = 0,041). Conclusion:Sterilization selection in reproductive age couples at Dr. Mohammad Hoesin Palembang Hospitalis influenced by female knowledge and husband support. Keywords:sterilization, tubal ligation, vasectomy, reproductive age couple